+0  
 
0
598
1
avatar

m=2-sqrt(3)       

 

m.(4-m).(2-m)/sqrt(3)

Guest Dec 24, 2015

Best Answer 

 #1
avatar+93289 
+9

m=2-sqrt(3)       

 

\(m.(4-m).(2-m)/sqrt(3)\\~\\ =\frac{m.(4-m).(2-m)}{\sqrt3}\\ \mbox{sub in }m=2-\sqrt3\\ =\frac{(2-\sqrt3)(4-(2-\sqrt3)).(2-(2-\sqrt3))}{\sqrt3}\\ =\frac{(2-\sqrt3)(2+\sqrt3).\sqrt3}{\sqrt3}\\ =(2-\sqrt3)(2+\sqrt3)\\ =4-3\\ =1\)

Melody  Dec 25, 2015
edited by Melody  Dec 25, 2015
 #1
avatar+93289 
+9
Best Answer

m=2-sqrt(3)       

 

\(m.(4-m).(2-m)/sqrt(3)\\~\\ =\frac{m.(4-m).(2-m)}{\sqrt3}\\ \mbox{sub in }m=2-\sqrt3\\ =\frac{(2-\sqrt3)(4-(2-\sqrt3)).(2-(2-\sqrt3))}{\sqrt3}\\ =\frac{(2-\sqrt3)(2+\sqrt3).\sqrt3}{\sqrt3}\\ =(2-\sqrt3)(2+\sqrt3)\\ =4-3\\ =1\)

Melody  Dec 25, 2015
edited by Melody  Dec 25, 2015

9 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.